2015
DOI: 10.2166/wst.2015.299
|View full text |Cite
|
Sign up to set email alerts
|

The urban harvest approach as framework and planning tool for improved water and resource cycles

Abstract: Water and resource availability in sufficient quantity and quality for anthropogenic needs represents one of the main challenges in the coming decades. To prepare for upcoming challenges such as increased urbanization and climate change related consequences, innovative and improved resource management concepts are indispensable. In recent years we have developed and applied the urban harvest approach (UHA). The UHA aims to model and quantify the urban water cycle on different temporal and spatial scales. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Urban water reuse is an inevitable solution to scarcity in irrigation water, especially in the delta regions due to its availability, freshwater character, and its richness with nutrients essential for agricultural production. Research indicated that water reuse could help cities and surrounding areas in closing water cycle and decrease the water demand to improve their water self-sufficiency (Agudelo-Vera et al, 2012;Leusbrock et al, 2015). Upgraded wastewater can be cascaded to nearby agriculture in the delta areas to provide with freshwater and nutrients and help to mitigate salinization.…”
Section: Introductionmentioning
confidence: 99%
“…Urban water reuse is an inevitable solution to scarcity in irrigation water, especially in the delta regions due to its availability, freshwater character, and its richness with nutrients essential for agricultural production. Research indicated that water reuse could help cities and surrounding areas in closing water cycle and decrease the water demand to improve their water self-sufficiency (Agudelo-Vera et al, 2012;Leusbrock et al, 2015). Upgraded wastewater can be cascaded to nearby agriculture in the delta areas to provide with freshwater and nutrients and help to mitigate salinization.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles referred to teach the proper use of water, changing consumption by providing incentives and creating a culture in order to influence the knowledge, attitude and perception of people and, as a result, making changes in people's behavior, creating social campaigns to conserve water and promoting a culture of saving. 24,34,[36][37][38][39][40][41] Management and Policymaking Methods Some articles have suggested adapting water resources management practices to climatic conditions, 19,27,31,[42][43][44][45][46][47] water demand management, setting pricing policies to reduce demand, 24.25,44,48-51 enforcing rules to restrict water use to high-consumption subscribers, 25,33,47,51,52 applying incentive policies such as discounts to people who consume the most, 20 rainwater collection, [53][54][55][56][57][58][59][60][61][62][63] virtual water trade 22,64,65 and in general optimizing consumption methods. 38 Apparently, any action at the household and community level reducing water consumption and controlling its consumption can reduce the pressure on water resources.…”
Section: Culture and Educationmentioning
confidence: 99%
“…Three strategies of technological innovation for water use efficiency show promise for Vietnamese industrial zones (Agudelo-Vera et al, 2012;Leusbrock et al, 2015;Levidow et al, 2016): (1) demand minimization through efficient "end-of-pipe" technologies (Ozturk et al, 2016); (2) "cascading" reclaimed water flows for low quality reuse (Agudelo-Vera et al, 2012;Luckmann et al, 2016); and (3) multi-sourcing from primary ground or surface water sources and secondary water sources such as rain water (Agudelo-Vera et al, 2012;GhaffarianHoseini et al, 2016). These…”
Section: Introductionmentioning
confidence: 99%
“…Three strategies of technological innovation for water use efficiency show promise for Vietnamese industrial zones (Agudelo‐Vera et al., 2012; Leusbrock et al., 2015; Levidow et al., 2016): (1) demand minimization through efficient “end‐of‐pipe” technologies (Ozturk et al., 2016); (2) “cascading” reclaimed water flows for low quality reuse (Agudelo‐Vera et al., 2012; Luckmann et al., 2016); and (3) multi‐sourcing from primary ground or surface water sources and secondary water sources such as rain water (Agudelo‐Vera et al., 2012; GhaffarianHoseini et al., 2016). These technologically driven strategies are linked to the wider principles of industrial ecology and symbiosis, aimed at enhancing circular resource flows in the processing and manufacturing sectors through cooperative strategies that enable by‐product exchange and utility sharing for resource efficiency (Jiao & Boons, 2017; Mol & Dieu, 2006; Spekkink, 2013).…”
Section: Introductionmentioning
confidence: 99%